Aerosol pH associated with preterm birth risk: Unmasking the hidden role of atmospheric acidity in maternal-fetal health - Bin Han; Yanting Chen; Jia Xu; Xinhua Wang; Liyao Guo; Ying Xu; Xiaoyu Pan; Zhipeng Bai (Environmental Pollution, 2026)

Cloud-based ligand-guided virtual screening with deep-learning-enhanced docking identifies a micromolar CXCR4 antagonist - Nonthaneth Nalinratana; Monsin Sangsawat; Kian Chee Chong; Yichun Xu; Junsong Han; Yanting Ding; Zhai Cai; Worathat Thitikornpong; Hua Zhu; Opa Vajragupta; Pornchai Rojsitthisak (Molecular Diversity, 2026)

Evolutionary auxiliary optimization for feature selection with multi-indicator task construction - Weizheng Zhang; Yiwei Zhao; Haotian Ning; Weiwei Zhang; Yanting Li; Yanpei Liu; Chuang Han (Swarm and Evolutionary Computation, 2026)

Amphiregulin as a central dynamic network biomarker in inhaled polyhexamethylene guanidine triggered pulmonary fibrosis - Jianzhong Zhang; Xin Li; Yuxin Ma; Wanjun Zhang; Zihao Han; Yanting Li; Jiayin Sun; Siqi Wang; Wei Han; Jing Liu; Yuxin Zheng; Jinglong Tang (Journal of Hazardous Materials, 2026)

Inorganic Arsenic Attenuates Crystalline Silica-Induced Pulmonary Inflammation and Fibrosis by Ameliorating Autophagolysosomal Dysfunction in Alveolar Macrophages - Yi Luo; Wei Su; Yong Luo; Yanting Han; Shuwen Gong; Fuhai Shen; Yulan Jin; Yi Guan; Xinyuan Zhao; Jinlong Li (Biological Trace Element Research, 2026)

Diesel exhaust induces hepatic steatosis by activating the aryl hydrocarbon receptor/CD36 pathway - Qian Song; Xueying Zhang; Yanting Li; Zixuan Liang; Ao Han; Xiaoran Wei; Xiaowen Tang; Juntong Wei; Wei Han; Shanfa Yu; Hongna Zhang; Yuxin Zheng (Journal of Hazardous Materials, 2026)

Deciphering the acute toxicity mechanisms of PFAS in algae: A molecular descriptor and binding energy hierarchy perspective - Yanting Li; Lin Zhao; Lu Wang; Han Zhang; Guodong Xing; Jinrui Yuan; Yongkui Yang; Peizhe Sun (Journal of Hazardous Materials, 2025)

Reply to “Methodological appraisal of estimating the prevalence and related factors of antenatal depression in China” - Chen Zhang; Chenchi Duan; Han Liu; Hualin Xu; Cheng Li; Jianxia Fan; Hong Li; Xiangjuan Li; Yi Guo; Yeping Wang; Xiufeng Li; Jing Li; et al. (Science Bulletin, 2025)

Biodegradation of aflatoxin B1 and ochratoxin A by Aspergillus sp. OA3, a novel fungal strain isolated from Fu brick tea - Yike Han; Ting Liu; Yanting Chen; Jingyi Ren; Xingnan Wang; Hongcai Li; Wenzhi Lei; Yuanye Liu; Ruisen Dai; Chunfeng Guo; Zhenpeng Gao (Food Bioscience, 2025)

Release, digestion and fermentation properties of polyphenols bound to sea buckthorn polysaccharides: Mechanistic explorations from integrated in vitro and in vivo studies - Xingnan Wang; Yanting Chen; Yike Han; Shiqi Li; Hongcai Li; Yuanye Liu; Wenzhi Lei; Guangquan Liu; Zhenpeng Gao (Carbohydrate Polymers, 2025)

Corrigendum to “Multichannel nerve conduit based on chitosan derivates for peripheral nerve regeneration and Schwann cell survival” [Carbohydrate Polymers 301 (2023) 120327] - Zhiwen Jiang; Yijie Zhang; Yanting Wang; Shuo Wang; Jing Chang; Wanshun Liu; Baoqin Han (Carbohydrate Polymers, 2025)

Targeting the mitochondrial-autophagy axis in pituitary neuroendocrine tumors via intracellular copper overload - Yao Feng; Han Wang; Hanyang Zhou; Ni Li; Yanting Liu; Yang Lu; Zhe Bao Wu; Dalong Ni; Li Xue (Chemical Engineering Journal, 2025)

Prevalence and related factors of antenatal depression in 11 provinces and cities of China: a 100,000 population-based study - Chen Zhang; Chenchi Duan; Han Liu; Hualin Xu; Cheng Li; Jianxia Fan; Hong Li; Xiangjuan Li; Yi Guo; Yeping Wang; Xiufeng Li; Jing Li; et al. (Science Bulletin, 2025)

Microbial communities and metabolite dynamics in the flowering fermentation of Fu brick Tea: Correlations with mycotoxin degradation - Yike Han; Xingnan Wang; Hongcai Li; Yuanye Liu; Mengzhen Han; Yanting Chen; Jingyi Ren; Ting Liu; Yan Liang; Xin Hu; Guimei Chen; Chunfeng Guo; et al. (Food Bioscience, 2025)

Metabolomics and volatilomics unravel the signature of pivotal bioactive metabolites in sea buckthorn juice and pomace under hydrolysis of cellulase and pectinase - Xingnan Wang; Jingyi Ren; Yanting Chen; Ting Liu; Hongcai Li; Wenzhi Lei; Yike Han; Shiqi Li; Xiaoning Tu; Bin Zhang; Guangquan Liu; Zhenpeng Gao (Food Bioscience, 2025)

Multifunctional carboxymethyl chitosan-based sponges loaded with epigallocatechin-3-gallate for accelerating wound healing in diabetic rats with full-thickness burns - Yanting Wang; Ziming Zhu; Xiansen Lv; Baoqin Han; Zhiwen Jiang (Carbohydrate Polymers, 2025)

Crocin-1 laden thermosensitive chitosan-based hydrogel with smart anti-inflammatory performance for severe full-thickness burn wound therapeutics - Xiansen Lv; Hui Li; Ya Chen; Yanting Wang; Jinhua Chi; Shuo Wang; Yan Yang; Baoqin Han; Zhiwen Jiang (Carbohydrate Polymers, 2024)

Microcystin-LR prenatal exposure induces coronary heart disease through macrophage polarization imbalance mediated by trophoblast-derived extracellular vesicles - Meihong Guo; Xinrui Li; Manhou Choi; Jingwen Zhang; Songci Yan; Danni Ma; Jing Zeng; Weidong Ding; Yanting Wen; Dongmei Li; Xiaodong Han; Yong Wang; et al. (Science of The Total Environment, 2024)

Mechanism underlying the role of integrin α3β1 in adhesive dysfunction between thyroid cells induced by diesel engine exhaust particles - Xiaoyin Guo; Siying Tang; Yanting Li; Chaohui Mu; Hongna Zhang; Qixiao Jiang; Menghui Jiang; Wei Han; Yuxin Zheng; Jinmei Piao (Science of The Total Environment, 2024)

Activation energy and organic matter structure characteristics of shale kerogen and their significance for the in-situ conversion process of shale oil - Wenxue Han; Xia Luo; Shizhen Tao; Senhu Lin; Jinzhong Liu; Yanting Yang (Fuel, 2024)

Analytical evaluation of stress–strain behavior of rubberized concrete incorporating waste tire crumb rubber - Xiaoyan Han; Shanshan Zhou; Aijiu Chen; Lingyun Feng; Yanting Ji; Zhihao Wang; Sheng Sun; Keliang Li; Xiaozhou Xia; Qing Zhang (Journal of Cleaner Production, 2024)

Geochemical behavior of C, N, and S in sediments of Hangzhou Bay, Southeastern China: implications for the study of paleoclimate and sea-level changes - Qin Gao; Alexander M. Piotrowski; Zilong Li; Pei Sun Loh; Cuicui Han; Zixuan Wang; Shihang Yang; Zengqing Guo; Dongqin Huang; Yanting Chen (Frontiers in Marine Science, 2024)
The correlation between the amount of organic carbon (OC) and sulfur (S) in sediments has been widely used as a paleosalinity indicator to distinguish between marine and freshwater environments. However, whether the ratio of total OC to total S (TOC/TS) can be used to identify unsteady or dynamic marine environments across sedimentary strata is still contended. An HZW1907 sediment core of 80 m in length was successfully collected in the middle of Hangzhou Bay (HZB), serving as one of the few boreholes that are crucial for the study of geologic and geo-environment changes in the coastal regions of eastern China since the Last Glacial Maximum (LGM). Total OC (TOC), stable carbon isotope, and TS of 82 subsamples from the HZW1907 core were analyzed to reconstruct the history of the shallow water biological pump and sulfur preservation record in the bay since the Late Pleistocene. Our results indicate that the samples had low concentrations of TOC (0.21%) and total nitrogen (TN) (0.02%), high mass ratio of TOC/TN (10.8), low δ 13 C (−24.9‰), low TS content (0.06%), and a high ratio of TOC/TS (9.1) from 33.6 ka BP to 12.3 ka BP, implying that freshwater organic matter (OM), algae, and C3 plant fragments were the main sources of OM in a relatively cold environment. The abundances of TOC, TN, and TS increased to 0.56%, 0.07%, and 0.4%, respectively, while δ 13 C (−23.9‰) increased and TOC/TS (2.7) decreased in the Holocene sediments, suggesting that seawater began to influence the composition of the sediments of HZB. Climate warming, which is likely to have impacted the results, was experienced from 12.3 ka BP. An OC isotope mixing model indicated that since the Mid-late Holocene, more than 70% of riverine OM accounted for the total OM. The TOC/TS ratio was identified as an effective indicator of seawater intrusion, with C/S ratios of 1–6 being considered to indicate a “sea–land transitional zone” sedimentary environment, a C/S >6 indicating freshwater, and a C/S<1 indicating normal marine facies. These findings provide crucial evidence for using TOC/TS to distinguish freshwater from marine environments and enhance our understanding of past climate changes. Therefore, these geochemical indicators can be used in conjunction with other sedimentary records to obtain accurate results about sedimentary evolution.

A comparison of milk fat globule membranes and whey proteomes: New insight into variation nutrient differences between Buffalo, Cow, Goat, and Yak - Lu Chen; Tiannuo Hong; Ziqi Li; Guohui Shen; Yanting Gu; Juan Han (Food Chemistry, 2023)

Biofortification of health-promoting glucosinolates in cruciferous sprouts along the whole agro-food chain - Mengyu Wang; Yubo Li; Yuhe Yang; Han Tao; Ghazala Mustafa; Fanliang Meng; Bo Sun; Jiansheng Wang; Yanting Zhao; Fen Zhang; Kejun Cheng; Qiaomei Wang (Trends in Food Science & Technology, 2023)

Identifying influential ships in multi-ship encounter situation complex network based on improved WVoteRank approach - Yanting Tong; Rong Zhen; Han Dong; Jialun Liu (Ocean Engineering, 2023)

The status of the global food waste mitigation policies: experience and inspiration for China - Guohui Shen; Ziqi Li; Tiannuo Hong; Xin Ru; Kunzhen Wang; Yanting Gu; Juan Han; Yanzhi Guo (Environment, Development and Sustainability, 2023)
Food waste has become a significant challenge faced by the community with a shared future for mankind, and it has also caused a considerable impact on China's food security. Scholars across disciplines, international organizations, and especially policymakers are increasingly interested in food waste. Policies are seen as a powerful factor in reducing food waste, but current research on related policies is more scattered. This paper summarizes and analyzes the experiences of food waste policy development and implementation by systematically reviewing the studies on food waste reduction policies. The results of this paper's analysis show that current global food waste policies are focused at the national strategic level, with approaches such as legislation, food donation, waste recycling, awareness and education, and data collection. At the same time, we find that the current experience of developed countries in policy formulation and implementation is beneficial for policy formulation in developing countries. And taking China as an example, we believe that developing countries can improve food waste policies in the future by improving legislation, guiding the development of food banks, promoting social governance, and strengthening scientific research projects. These policies will all contribute strongly to global environmental friendliness. In addition, we discuss some of the factors that influence the development of food waste policies and argue that in the future, more consideration needs to be given to the effects of policy implementation and that case studies should focus more on developing countries. This will contribute to the global sustainable development process.

Multichannel nerve conduit based on chitosan derivates for peripheral nerve regeneration and Schwann cell survival - Zhiwen Jiang; Yijie Zhang; Yanting Wang; Shuo Wang; Jing Chang; Wanshun Liu; Baoqin Han (Carbohydrate Polymers, 2023)

Unraveling Physiological and Metabolomic Responses Involved in Phlox subulata L. Tolerance to Drought Stress - Yan Xiong; Yanting Qu; Hui Han; Fei Chen; Li Li; Huanwei Tang; Daidi Che; Xing Zhang (Plant Molecular Biology Reporter, 2021)

Identification and association of novel lncRNA pouMU1 gene mutations with chicken performance traits - Tuanhui Ren; Yanting Zhou; Yu Zhou; Weihua Tian; Zhenzhen Gu; Song Zhao; Yadi Chen; Ruili Han; Xiaojun Liu; Xiangtao Kang; Zhuanjian Li (Journal of Genetics, 2017)

Effects of urbanization on gaseous and particulate polycyclic aromatic hydrocarbons and polychlorinated biphenyls in a coastal city, China: levels, sources, and health risks - Youwei Hong; Jinsheng Chen; Fuwang Zhang; Han Zhang; Lingling Xu; Liqian Yin; Yanting Chen (Environmental Science and Pollution Research, 2015)

Platelet-derived growth factor mediates interleukin-13-induced collagen I production in mouse airway fibroblasts - Jiamei Lu; Yanting Zhu; Wei Feng; Yilin Pan; Shaojun Li; Dong Han; Lu Liu; Xinming Xie; Guizuo Wang; Manxiang Li (Journal of Biosciences, 2014)